NLRP3 mediates the neuroprotective effects of SVHRSP derived from scorpion venom in rotenone-induced experimental Parkinson's disease model. (10th August 2023) - Zhang, Yu; Li, Sheng; Hou, Liyan; Wu, Mingyang; Liu, Jianing; Wang, Ruonan; Wang, Qingshan; Zhao, Jie
Abstract: Ethnopharmacological relevance: In traditional Chinese medicine, scorpion is used to treat diseases with symptoms such as trembling, convulsion and dementia. Our laboratory employs patented technology to extract and purify the active single component from scorpion venom. We then utilize mass spectrometry to determine the amino acid sequence of the polypeptide and synthesize it artificially to acquire the polypeptide with a purity of 99.3%, named SVHRSP (Scorpion Venom Heat-Resistant Peptide). SVHRSP has been demonstrated to display potent neuroprotective efficacy in Parkinson's disease. Aim of the study: To explore the molecular mechanisms and potential molecular targets of SVHRSP-afforded neuroprotection in PD mouse models, as well as to investigate the role of NLRP3 in SVHRSP-mediated neuroprotection. Materials and methods: The PD mouse model was induced by rotenone and the neuroprotective role of SVHRSP on the PD mouse model was measured using the gait test, rotarod test, the number of dopaminergic neurons, and the activation of microglia. RNA sequencing and GSEA analysis were performed to find the differentially biological pathways regulated by SVHRSP. Primary mid-brain neuron-glial cultures and NLRP3−/− mice were applied to verify the role of NLRP3 by using qRT-PCR, western blotting, enzyme-linked immunosorbent assay (ELISA) and immunostaining. Results: SVHRSP-afforded dopaminergic neuroprotection was accompanied with inhibition of microglia-mediated neuroinflammatory pathways. Importantly, depletion of microglia markedly reduced the neuroprotective efficacy of SVHRSP against rotenone-induced dopaminergic neurotoxicity in vitro. SVHRSP inhibited microglial NOD-like receptor pathway, mRNA expression and protein level of NLRP3 in rotenone PD mice. SVHRSP also reduced rotenone-induced caspse-1 activation and IL-1β maturation, indicating that SVHRSP mitigated activation of NLRP3 inflammasome. Moreover, inactivation of NLRP3 inflammasome by MCC950 or genetic deletion of NLRP3 almost abolished SVHRSP-afforded anti-inflammatory, neuroprotective effects and improvement of motor performance in response to rotenone. Conclusions: NLRP3 mediated the neuroprotective effects of SVHRSP in rotenone-induced experimental PD model, providing additional evidence for the mechanisms of SVHRSP-afforded anti-inflammatory and neuroprotective effects in PD. Graphical abstract: Image 1 Highlights: Verification of the key role of microglia in SVHRSP-afforded protection using RNA sequencing and in vitro and in vivo. Screening and identification of NLRP3 as a potential therapeutic target for SVHRSP-afforded neuroprotection. SVHRSP inhibited NLRP3 expression in vivo and in vitro. NLRP3 mediates the neuroprotective effects of SVHRSP against dopaminergic neurodegeneration in vivo and in vitro.